直线共轭齿轮泵的基本参数优化设计 - 徐学忠; 宋天麟 (Jixie chuandong)
The design parameter and formulation for calculating dimension in internal gear pump with straight line conjugated curve profile are discussed at first.Then a mathematic model for optimization of the design parameter of this pump,which takes the minimum fluctuation of flow and maximum flow per cubage of the pump as objective function,and contact ratio,pressure angle,profile overlapping and etc as constraint condition.By comparison the optimized design parameter of the two examples with others of this type of pump,the result is satisfactory and the result can be utilized in design same module and same number teeth.it gives a theory foundation for design of the pump.